Abstracts of oral and poster presentations given at the 4th Rusts of Forest Trees Conference, Florence, Italy, 3 –6 May 2010 - VV., AA. (Phytopathologia Mediterranea, 2011)
The 4th International Rusts of Forest Trees Conference was held in Florence, Italy, from May 3 to May 6, 2010. Florence is located in Tuscany, Central Italy, a region which was historically plagued by tree rust outbreaks. More than 40 tree rust specialists from 11 Countries from the northern as well as the southern hemisphere attended the meeting and gave 35 presentations on a broad array of topics, including phylogeny, distribution, biology, epidemiology, genomics, genetic resistance, and management.